Perioperative echocardiography‐derived right ventricle function parameters and early outcomes after tetralogy of Fallot repair in mid‐childhood: a single‐center, prospective observational study. Issue 11 (16th August 2016) - Raj, Ravi; Puri, Goverdhan Dutt; Jayant, Aveek; Thingnam, Shyam Kumar Singh; Singh, Rana Sandip; Rohit, Manoj Kumar
Abstract : Background: Right ventricular (RV) function alterations are invariably present in all patients after tetralogy of Fallot (TOF) repair. Unlike the developed world where most of the patients with TOF are corrected in infancy, average age of presentation and thus surgery for these patients in the developing world may be higher. We aimed to study the correlation between RV function parameters such as tricuspid annular peak systolic excursion (TAPSE), fractional area change (FAC), and tricuspid annular peak systolic velocity (S') with early outcome variables after intracardiac repair for TOF. Materials and Methods: Fifty patients with a preoperative diagnosis of tetralogy of Fallot scheduled for corrective surgery were included in this single‐center, prospective observational study. A preoperative transthoracic echocardiogram was performed to measure RV function parameters (FAC0, TAPSE0, S'0). Transthoracic echocardiography was repeated postoperatively to measure FAC1, TAPSE1, S'1 (day 1) and FAC2, TAPSE2, and S'2 (day 3). The relationship between preoperative and postoperative RV function parameters with in‐hospital mortality, duration of mechanical ventilation, and intensive care unit stay was studied. Results: The median age of patients was 6 years (range 1–14 years). Multiple stepwise logistic regression analysis showed RV FAC as best predictor of clinical outcome. Area under the receiver operating characteristic curve for postoperative RV function parameters, that is, FAC, TAPSE, and S' to predict early or delayed recovery was 0.944, 0.875, and 0.655, respectively. Conclusions: Among the RV function parameters studied, RV FAC best predicted the early outcome variables after TOF repair, followed by TAPSE while lateral tricuspid annular velocity S' being the least predictive.